Foundations of Software Science and Computation Structures 21st International Conference, FOSSACS 2018, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018. Proceedings - Baier, Christel; Dal Lago, Ugo (Theoretical Computer Science and General Issues,, 2018)
This book is Open Access under a CC BY licence.